Developing a Contextual Approach-Based Interactive E-LKPD with Liveworksheet for Arabic Language Learning - M. Dzikrul Hakim Al Ghozali; Farda Salsabila (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
The implementation of conventional teaching methods that fail to address students' needs has significantly contributed to low engagement and comprehension in Arabic language learning at Islamic Senior High School KH. Abd. Wahab Hasbulloh Jombang. This study aims to develop an interactive E-LKPD (Electronic Student Worksheet) using Liveworksheet with a contextual approach to enhance students' Arabic language proficiency. Employing a Research and Development (R&D) methodology with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), data were collected through interviews, observations, questionnaires, and tests. Data analysis incorporated both qualitative and quantitative descriptive methods, including normality tests, paired samples t-tests, and N-Gain tests. The developed E-LKPD effectively presents As-Safar learning materials interactively and contextually, integrating practice exercises through the Liveworksheet platform. Expert validation confirmed the high validity of both the content and instructional media. Furthermore, effectiveness testing demonstrated that the context-based E-LKPD using Liveworksheet significantly improves students' Arabic language comprehension, confirming its efficacy as an instructional tool.